2020
DOI: 10.3389/fpls.2020.597819
|View full text |Cite
|
Sign up to set email alerts
|

iTRAQ-Based Proteomic Analysis Reveals the Role of the Biological Control Agent, Sinorhizobium fredii Strain Sneb183, in Enhancing Soybean Resistance Against the Soybean Cyst Nematode

Abstract: The soybean cyst nematode (SCN), Heterodera glycines Ichinohe, poses a serious threat to soybean production worldwide. Biological control agents have become eco-friendly candidates to control pathogens. Our previous study indicated that the biocontrol agent, Sinorhizobium fredii strain Sneb183, may induce soybean resistance to SCN. To study the mechanisms underlying induced disease resistance in the plant by Sneb183, an iTRAQ (isobaric tag for relative and absolute quantitation)-based proteomics approach was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…When pathogens attacked plants, C4H has been confirmed to participate in the accumulation of flavonoids and isoflavones, and to enhance cell wall lignification and soybean resistance. 77 The stability of flavonols can be improved by catalytic glycosylation of flavonols through UDP-sugar-dependent glycosyltransferases (UGTs). 73,78 Furthermore, PPO dominates the conversions of flavonols glycosides and reduces their content.…”
Section: Discussionmentioning
confidence: 99%
“…When pathogens attacked plants, C4H has been confirmed to participate in the accumulation of flavonoids and isoflavones, and to enhance cell wall lignification and soybean resistance. 77 The stability of flavonols can be improved by catalytic glycosylation of flavonols through UDP-sugar-dependent glycosyltransferases (UGTs). 73,78 Furthermore, PPO dominates the conversions of flavonols glycosides and reduces their content.…”
Section: Discussionmentioning
confidence: 99%
“…Sinorhizobium fredii is another important biocontrol agent against H. glycines. Suspension of isolate Sneb183 was inoculated to soybean plants and reduced the numbers of juveniles and cysts and inhibited the egg hatching of H. glycines [117,118]. Another isolate, L396, also inhibited egg hatching and improved the mortality rate of H. glycines [119].…”
Section: Biocontrol Bacteria Against Soybean Cyst Nematode Diseasementioning
confidence: 99%
“…Soybean seeds of susceptible cultivars treated with the Snef1650 fermentation liquid demonstrated increased SCN tolerance and a boost in growth and yield. Studies have demonstrated that microorganismtreated seeds produce nematicides during root development and resist infection due to different parasitic nematodes through systemic or local induction of endogenous hormones and plant defense-related proteins in the plant immune system [32][33][34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%